PENCEGAHAN PENYEBARAN VIRUS COVID-19 DI KELURAHAN PANDEYAN KEMANTREN UMBULHARJO - Paiman, Paiman; Putra, Aji Permana; Kristiyanto, Hery (Gemi: Jurnal Penelitian dan Pengabdian, 2021)
The Covid-19 pandemic has made UCY as a campus with an Islamic spirit and with a national perspective to care by being involved in government activities, namely preventing this outbreak with thematic KKN activities. Thematic KKN is the orientation of its program of activities focused on certain fields in accordance with social problems and the direction of development policies organized by the government. This time the activity is focused on fighting this pandemic in accordance with the prevention protocol and assistance for both medical devices and basic necessities.